2011
DOI: 10.1007/s10396-011-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of procedures for decontaminating ultrasound probes

Abstract: Improperly decontaminated ultrasound probes can transmit bacteria among patients. Ultrasound probes should be decontaminated by wiping with a paper towel after examinations to prevent bacterial transmission. Plain or ethanol-soaked paper towels should be used depending on the situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Our previous study also confirmed that unwiped ultrasound probes could become contaminated with bacteria that might be transmitted from patient to patient [6]. That study detected coagulase-negative Staphylococcus (CNS) from as major bacterial species transmitted via ultrasound probes, followed by Corynebacterium species, Bacillus species, and Staphylococcus aureus including Methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Bacterial Contamination Via Ultrasound Probessupporting
confidence: 70%
See 2 more Smart Citations
“…Our previous study also confirmed that unwiped ultrasound probes could become contaminated with bacteria that might be transmitted from patient to patient [6]. That study detected coagulase-negative Staphylococcus (CNS) from as major bacterial species transmitted via ultrasound probes, followed by Corynebacterium species, Bacillus species, and Staphylococcus aureus including Methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Bacterial Contamination Via Ultrasound Probessupporting
confidence: 70%
“…Our study showed that bacterial transmission could be almost completely prevented by wiping ultrasound probes with an alcohol-soaked paper towel [6]. Again, frequent alcohol disinfection can cause ultrasound probes to break down and impaired imaging [8], so wiping probes with alcohol-soaked paper towel after every examination may be a limited driving-force in clinical practice.…”
Section: Procedures For Decontaminating Ultrasound Probesmentioning
confidence: 72%
See 1 more Smart Citation
“…By now, there is no consensus regarding these protocols for rheumatology settings. Reports of infectious diseases transmitted via probe or associated with the use of transmission gel occur more frequently in surgical healthcare settings, in patients with unhealed wounds, burns and those in intensive care units [24,25,41,42]. Some recent general guidelines which include the obligation of using sterile gel were proposed in order to minimize the infection risk [43].…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive use of the same transducer in different anatomic areas or between different patients, the small distance between the transducer and injection site raises the question for the true risk of septic complications when performing these kinds of manoeuvres [22][23][24][25][26]. On the other hand, sophisticated disinfection protocols are time consuming and expensive and, at the end, may limit the number of performing physicians.…”
Section: Introductionmentioning
confidence: 99%